2010
DOI: 10.1016/j.it.2009.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The immunology of fibrosis: innate and adaptive responses

Abstract: Fibrosis is an important health problem and its pathogenetic principles are still largely unknown. It can develop either spontaneously or, more frequently, as a consequence of various underlying diseases. However, irrespective of the primary cause, fibrotic tissue is always infiltrated by mononuclear immune cells. In most instances the reason for the attraction of these cells to fibrotic tissue and their proliferation remains to be determined, however their cytokine profile shows clear-cut proinflammatory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
160
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(167 citation statements)
references
References 105 publications
(100 reference statements)
3
160
1
3
Order By: Relevance
“…Local pulmonary inflammatory activity is reflected by elevated circulating levels of inflammatory cytokines (IL-1, IL-6) and chemokines (IL-8) as well as C-reactive protein that may correlate with a worse clinical outcome (Dorfműller et al, 2003;Soon et al, 2010;Kherbeck et al, 2011). An autoimmune etiology of PAH is further supported by PAH development in individuals with scleroderma-like disorders with established autoimmune phenotype and the presence of antinuclear antibodies and autoantibodies directed against EC and fibroblasts (Wick et al, 2010;Kherbeck et al, 2011;Bussone et al, 2012). Moreover, PAH has been associated with a lack of CD4+ T cells, specifically T cells with a regulatory phenotype (Treg) in affected lungs that would normally function to limit vascular endothelial injury and inflammatory/autoimmune activity and hence prevent pulmonary hypertension (Tamosiuniene et al, 2011).…”
Section: Role Of the Immune System In The Pathogenesis Of Pahmentioning
confidence: 99%
“…Local pulmonary inflammatory activity is reflected by elevated circulating levels of inflammatory cytokines (IL-1, IL-6) and chemokines (IL-8) as well as C-reactive protein that may correlate with a worse clinical outcome (Dorfműller et al, 2003;Soon et al, 2010;Kherbeck et al, 2011). An autoimmune etiology of PAH is further supported by PAH development in individuals with scleroderma-like disorders with established autoimmune phenotype and the presence of antinuclear antibodies and autoantibodies directed against EC and fibroblasts (Wick et al, 2010;Kherbeck et al, 2011;Bussone et al, 2012). Moreover, PAH has been associated with a lack of CD4+ T cells, specifically T cells with a regulatory phenotype (Treg) in affected lungs that would normally function to limit vascular endothelial injury and inflammatory/autoimmune activity and hence prevent pulmonary hypertension (Tamosiuniene et al, 2011).…”
Section: Role Of the Immune System In The Pathogenesis Of Pahmentioning
confidence: 99%
“…3 Fibrous encapsulation can develop at almost all interfaces of implanted biomaterials since it comprises overlapping stages similar to those in wound healing and tissue repair. 4 In addition, it was also reported that aggressive fibroblasts at bone surface can produce multiple cytokines to activate osteoclastogenesis, suppress osteoblast functions, and induce local inflammation, which may subsequently cause osteolysis and implant aseptic loosening. [5][6][7] Although fibrous encapsulation can impair osseointegration and the success of orthopedic implants, it receives insufficient attention in scientific and clinical research.…”
mentioning
confidence: 99%
“…Moreover, thrombin has been linked to the production of procollagen (11) and the expression of connective tissue growth factor (CTGF), a crucial fibrotic factor, in lung fibroblasts via the proteaseactivated receptor 1 (PAR-1) (11,12). One of the main cell types that contribute to fibrosis via collagen production is myofibroblasts (16,17). Although they originate from the differentiation of several cell populations in different tissues, they share a common function (18), producing profibrotic mediators.…”
mentioning
confidence: 99%